2015
DOI: 10.1038/ncomms7431
|View full text |Cite
|
Sign up to set email alerts
|

ERK phosphorylation and miR-181a expression modulate activation of human memory TH17 cells

Abstract: T helper (T H ) cell polarization during priming is modulated by a number of signals, but whether polarization to a given phenotype also influences recall responses of memory T H cells is relatively unknown. Here we show that miR-181a is selectively induced in both human and mouse naive T cells differentiating into the T H 17, but not T H 1 or T H 2 subset. In human memory T H 17 cells, miR-181a regulates responses to cognate antigens through modulation of ERK phosphorylation. By enhancing the signalling casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 52 publications
4
26
0
Order By: Relevance
“…However the biological consequence and relevance of lowered Erk activity upon TCR reactivation leading to lowered FasL protein and reduced caspase activity in Th17 cells suggest direct proof of principle for their AICD resistance and higher incidence in inflammatory diseases including psoriasis, RA, inflammatory bowel disease and multiple sclerosis [3639]. Evidence from other groups and ours (unpublished data) suggest that lowered Erk activity post TCR activation tends to favor Th17 propagation [40, 41] and Erk2 enhancement sensitizing Th17 cells to TCR AICD has major consequence attached.…”
Section: Discussionmentioning
confidence: 95%
“…However the biological consequence and relevance of lowered Erk activity upon TCR reactivation leading to lowered FasL protein and reduced caspase activity in Th17 cells suggest direct proof of principle for their AICD resistance and higher incidence in inflammatory diseases including psoriasis, RA, inflammatory bowel disease and multiple sclerosis [3639]. Evidence from other groups and ours (unpublished data) suggest that lowered Erk activity post TCR activation tends to favor Th17 propagation [40, 41] and Erk2 enhancement sensitizing Th17 cells to TCR AICD has major consequence attached.…”
Section: Discussionmentioning
confidence: 95%
“…127,131 The expression of miR-181a is lower in naive T-helper cells as compared to thymocytes, and it further declines upon TCR activation and cell differentiation. 128 Since TCR signal strength is known to determine Tfh cell differentiation 132 and a recent study indicated that the miR-181a target DUSP6 inhibits Tfh cell differentiation, 133 it is possible that miR-181a may also regulate Tfh cells. 127,129 An additional study showed that miR-181a is highly expressed in Th17 cells and that it regulates the TCR signaling threshold specifically in Th17 cells as compared to Th1 or Th2 cells.…”
Section: P Otentialrole Sforother Mirna Sinthereg Ul Ati Onoftfhcelmentioning
confidence: 99%
“…126 Several studies showed that miR-181a regulates the TCR signaling threshold of T-helper cells. [127][128][129][130] miR-181a is highly expressed in thymocytes, where it facilitates positive selection. 127,131 The expression of miR-181a is lower in naive T-helper cells as compared to thymocytes, and it further declines upon TCR activation and cell differentiation.…”
Section: P Otentialrole Sforother Mirna Sinthereg Ul Ati Onoftfhcelmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr. Silvia Monticelli (Institute for Research in Biomedicine, Bellinzona, Switzerland) discussed how miRNAs play an important role in affecting the ability of naïve CD4 T cells to differentiate into a number of different memory and effector subsets. Specifically, she showed that miR-181a was selectively induced in both human and mouse naïve T cells differentiating into the T H 17 subset(13). In T H 17 cells, miR-181a also regulated responses to cognate antigens through modulation of ERK phosphorylation.…”
mentioning
confidence: 99%